Prácticas de presupuesto de capital: evaluación empírica en un grupo de empresas del sector de la construcción en Colombia (2014)
The empirical analysis of capital budgeting or investment appraisal is a topic that has been widely studied in developed countries, such as the United States, the United Kingdom, and Canada. The documentation of these practices in emerging countries is scarce. This paper provides some information about current capital budgeting techniques through an empirical study of practices in a group of Colombian companies in the construction industry. In the companies surveyed it was found that 86% of professionals use the most recommended methods in the literature, such as the Internal Rate of Return (IRR) and Net Present Value (NPV), with a preference for the IRR (50% always use it) over the NPV (36% always use it). It was also found that 95% lack knowledge of more sophisticated methods, such as Real Options (OR). Most of the respondents subjectively determine the discount rate that is used for evaluation, indicating the lack of any theoretical justification to determine an appropriate rate.